Improving heat exchanger efficiency using the pulsed method of cleaning - A. I. Haibullina; N. X. Zinnatullin; V. K. Ilyin (Известия высших учебных заведений: Проблемы энергетики)
The fouling of heat exchange equipment leads to serious economic losses in many industries, therefore to find a method to reduce deposits on heat transfer surfaces remains an actual task. THE PURPOSE. In this paper, a practical solution is proposed for the implementation of a pulsating cleaning method of oil coolers as an example. METHODS. The influence ofpulsations on cleaning of the external surface of the heat exchanger is studied by computer modeling with Ansys Fluent. The fluid flow was described by the Navier-Stokes equation, particle motion and their interaction was described by the discrete element method (DEM). In the study, a staggered tube bundle was considered. The pulse frequency 0.3125 Hz, the amplitude referred to the diameter of tube is 35, the Reynolds number 100, the duty cycle of the pulsations 0.25.Oil was chosen as the medium. RESULTS. Evaluation of the pulsating cleaning method was carried out on the basis of the analysis of the mechanics of particle collisions on the surface of the central cylinder in the beam, with stationary and pulsating flow. It was found that the pulsating flow helps to reduce deposits in the front of the cylinder and is not effective in the back. CONCLUSHION. An analysis of the mechanics of particle impact on the heat exchange surface showed that this pulsation mode is more effective for removing plastic deposits.